ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL BERBASIS FLIPPED CLASSROOM DI SEKOLAH DASAR - Khusna, Mufidatul; Febrianto, Priyono Tri (Hijri, 2023)
The purpose of this study is to describe the need for the development of flipped classroom-based e-modules in elementary schools. This type of research is descriptive qualitative research. The subjects in this study were grade IV teachers and 31 grade IV students for the 2023/2024 school year, UPTD SDN Keleyan 1, Socah District, Bangkalan Regency, East Java, consisting of 16 men and 15 women. Data collection techniques include observation, interviews, and questionnaires. The data analysis used is Miles and Huberman's qualitative data analysis which consists of data collection, data reduction, data presentation, and conclusions. Based on observations and interviews, it can be seen that teachers only use teaching materials in the form of Curriculum Merdeka textbooks provided by the school. In addition, the results of the student needs questionnaire stated that out of 31 students, 25 students (80.64%) were happy if they could learn using teaching materials other than the Curriculum Merdeka textbook, then out of 31 students, 25 students (80.65%) had never learned to use electronic modules. Furthermore, out of 31 students, 31 students (100%) said they were happy if they could study and do assignments with their friends in class. Based on the results of the study, it can be concluded that it is necessary to develop flipped classroom-based e-module teaching materials, with flipped classroom-based e-modules can make students independent, active, think critically, and collaboratively in learning.